Perubahan Sosial : Alih Fungsi Lahan pada Masyarakat Bekasi - Simatupang, Liyola; Rizki Setiawan (Sociology Study Program, Faculty of Social Science and Law, Universitas Negeri Jakarta, 2022)
Empty land or plantation land in suburban cities has been traded and various facilities have been built in the form of facilities and infrastructure to support urban development. Developments in the form of road construction, city parks, clusters, fashion outlets, restaurants, and others have been built so that they have an impact on people's lives. This article aims to describe the suburbs of Bekasi and find out what impacts and changes in social life occur due to developments in the suburbs. This study uses a qualitative research with a descriptive approach. This research was conducted in the vicinity of Bina Asih, Jatiasih District, Bekasi City, West Java Province. Data collection techniques through interviews, observation, and documentation. The results of the study show that the initial development in Jatiasih District began with the construction of the Outer Ring Road Toll Road which had started operating in 2007, then over time the vacant land changed its function from agriculture to housing construction and supporting facilities such as hospitals, restaurants, outlets. fashion, and others. The impact of this development is an increase in population, cases of theft, and the waning of the value of mutual cooperation. Social changes that occur are diverse livelihoods and consumption society.